2014
DOI: 10.1007/s00442-014-2889-7
|View full text |Cite
|
Sign up to set email alerts
|

Human-resource subsidies alter the dietary preferences of a mammalian top predator

Abstract: Resource subsidies to opportunistic predators may alter natural predator-prey relationships and, in turn, have implications for how these predators affect co-occurring prey. To explore this idea, we compared the prey available to and eaten by a top canid predator, the Australian dingo (Canis lupus dingo), in areas with and without human-provided food. Overall, small mammals formed the majority of dingo prey, followed by reptiles and then invertebrates. Where human-provided food resources were available, dingoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 59 publications
0
74
1
Order By: Relevance
“…Despite this observation at the burrow-system, great desert skink still formed a relatively high proportion of dingo diet with 14% of dingo scats containing the remains of this species. Although an analysis of 12 000 dingo scats over a 20-year period found that, across most of Australia, medium-sized mammals are the preferred prey of dingoes (Corbett 1995), within arid environments reptiles have been found to be a dominant part of the dingo diet (Paltridge 2002;Newsome et al 2014). In support of this, we found that 62.5% of scats contained reptile remains (25% goanna, 21% skink exclusive of great desert skink; 10% dragon, 1.5% snake, 3% other reptile) compared with 15% of scats that contained the remains of mammals.…”
Section: Relative Predator Impact On Great Desert Skinkmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this observation at the burrow-system, great desert skink still formed a relatively high proportion of dingo diet with 14% of dingo scats containing the remains of this species. Although an analysis of 12 000 dingo scats over a 20-year period found that, across most of Australia, medium-sized mammals are the preferred prey of dingoes (Corbett 1995), within arid environments reptiles have been found to be a dominant part of the dingo diet (Paltridge 2002;Newsome et al 2014). In support of this, we found that 62.5% of scats contained reptile remains (25% goanna, 21% skink exclusive of great desert skink; 10% dragon, 1.5% snake, 3% other reptile) compared with 15% of scats that contained the remains of mammals.…”
Section: Relative Predator Impact On Great Desert Skinkmentioning
confidence: 99%
“…Below average annual rainfall was recorded at the study site in 2013 (299.5 mm; 12 months prior to the collection of scats) possibly reducing the numbers of small mammals available during the study period. In addition, seasonal conditions are known to influence dingo diet in central Australia, where mammals form a larger part of dingo diets in the winter months when many reptile species are hibernating, and reptiles forming the majority of dingo diet in the summer months (Newsome et al 2014).…”
Section: Relative Predator Impact On Great Desert Skinkmentioning
confidence: 99%
“…Among species, supplementary food can alter species relationships to the extent that community composition shifts (Brown and Munger 1985, Boutin 1990. In addition, supplementary food may enhance or reduce predation risk (Dahle et al 1998, Takimoto et al 2002, Preston and Rotenberry 2006, Borgmann et al 2013, Newsome et al 2014, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In the maned wolf, however, non-digestible anthropogenic waste (e.g., plastic) has been found to comprise 14.1% of all diet items [40] and to be present in up to 40% of scats [41]. Similar studies on dingoes indicate that the probability of a scat sample containing rubbish is relatively high at 17% [14]. Elephants (Elaphus maximus) have been observed feeding at garbage dumps in India [42] and Sri Lanka [43] and, while little is known about the consequences of this behaviour on elephant health, plastic waste is spread via their dung and may then be consumed by other wildlife (T. Thekaekara, The Shola Trust pers comm.…”
Section: Other Impacts To Wildlife Healthmentioning
confidence: 86%
“…provide ideal examples to highlight such effects. In the case of dingoes, access to large quantities of food scraps at a waste facility resulted in decreased home-ranges and movements, larger group sizes, increased rates of inbreeding, and changes to their sociality and habitat use [14][15][16][17]. Moreover, the population of subsidised dingoes was a genetically distinct cluster, possibly because of founder effects [15].…”
Section: Direct Effects On Wildlife Ecology and Behaviourmentioning
confidence: 99%